Korai és időskori halálozások különbségei Európában a 2000-es évek első évtizedében; Disparities in premature and old age mortality in Europe in the first decade of the 2000s - Mária Lackó (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
– This study presents disparities in mortality rates of 38-41 European countries and attempts at giving explanations for these. Explanatory factors of premature (0-64 ages) and old age (above 65 years old) mortality rates are compared accordig to causespecific diseases and genders for 2009. In addition, mortality disparities due to avoidable (preventable and treatable) diseases are analyzed on a narrower sample of countries for 2015. The model applied in the investigations takes into account the living conditions and life-styles of the population in the given countries i.e. GDP per capita, geographical location, air-pollution, educational level, tobacco and spirit consumption habits, and health care expenditures. The most astonishing result is connected with the effect of air pollution: this factor has a similarly big weight in increasing premature male mortality as the wellknown factor, tobacco consumption. Moreover, in the case of old age male mortality air pollution even dominate the effect of smoking.
Keywords: I12; I15; O57; 330; Premature and Old Age Mortality; Cross-country Comparison; Europe